Arsenic pollution remediation mechanism and preliminary application of arsenic-oxidizing bacteria isolated from industrial wastewater. (1st May 2023) - Zhao, Mengmeng; Zheng, Gege; Kang, Xiuyun; Zhang, Xiaoyan; Guo, Junming; Zhang, Mingxia; Zhang, Jingwen; Chen, Yiping; Xue, Lingui
Abstract: Microbial remediation is vital for improving heavy metal-polluted water. In this work, two bacterial strains, K1 ( Acinetobacter gandensis ) and K7 ( Delftiatsuruhatensis ), with high tolerance to and strong oxidation of arsenite [As(III)], were screened from industrial wastewater samples. These strains tolerated 6800 mg/L As(III) in a solid medium and 3000 mg/L (K1) and 2000 mg/L (K7) As(III) in a liquid medium; arsenic (As) pollution was repaired through oxidation and adsorption. The As(III) oxidation rates of K1 and K7 were the highest at 24 h (85.00 ± 0.86%) and 12 h (92.40 ± 0.78%), respectively, and the maximum gene expression levels of As oxidase in these strains were observed at 24 and 12 h. The As(III) adsorption efficiencies of K1 and K7 were 30.70 ± 0.93% and 43.40 ± 1.10% at 24 h, respectively. The strains exchanged and formed a complex with As(III) through the –OH, –CH3, and C]O groups, amide bonds, and carboxyl groups on the cell surfaces. When the two strains were co-immobilized with Chlorella, the adsorption efficiency of As(III) improved (76.46 ± 0.96%) within 180 min, thereby exhibiting good adsorption and removal effects of other heavy metals and pollutants. These results outlined an efficient and environmentally friendly method for the cleaner production of industrial wastewater. Graphical abstract: Image 1 Highlights: Bacteria K1 and K7 with high tolerance and oxidation to arsenite were isolated. K1 and K7 remediate arsenic pollution through oxidation and adsorption. K1 and K7 can well remediated industrial sewage after co-fixation with Chlorella. This study opens up a new way for cleaner production of sewage treatment.